Características microbiológicas e físico-químicas do queijo tipo “minas frescal” de leite de cabras suplementadas com premix® - Bernardino, Ariana Marinho (2016)
This research was developed aiming to evaluate the microbiological and physicochemical characteristics of the cheese frescal mines, prepared with goat milk supplemented with vitamins, minerals, amino acids, pre and probiotics (PREMIX®). A Latin Square experimental design was developed with 12 goats, using the containment system, where they received diet and increasing concentrations of PREMIX®, distributed in the following treatments: T1 = 0%; T2 = 0.5%; T3 = T4 = 1% and 1.5%. The milk and cheese produced were subjected to proximate composition and microbiological analysis. We evaluated the consumption of dry matter (CMS), water consumption (CA) and milk production (PL). It conducted feeding behavior evaluating the behavioral parameters: leisure (O), eating (C) and rumination (R). The physiological variables as excretion of feces (FEZ), urinary frequency (URI) and search for water (AGUA) were also evaluated in this study. It was calculated profitability in milk production costs and cheese, noting the average gross revenue (RBM), average gross margin (MBM) and average profitability (RM). Cheese yield was also evaluated. There was no significant difference in CMS, CA and not in PL. The behavioral analysis, were not significant variations observed. The costs in the production of milk and cheese were not affected regarding the use of PREMIX® as well as the yield of the cheese. Moreover, it was observed that the supplement ranged the milk fat content, not affecting the other components. Already the results for the cheeses, there was variation to ashes, humidity, pH and calcium, and other constituents without significant changes. As for microbiological evaluation, milk and cheese remained within the standards established by law. Therefore, it is concluded that the PREMIX® does not influence the consumption or the production of milk, but alters lipid percentage of milk constituents and some of the cheese.